An in vitro model to study immune activation, epithelial disruption and stromal remodelling in inflammatory bowel disease and fistulising Crohn’s disease - Mobbs, Claire L.; Darling, Nicole J.; Przyborski, Stefan (Frontiers in Immunology, 2024)
At present, preclinical models of inflammatory bowel disease (IBD) are insufficient, limiting translation between research and new therapeutics. This is especially true for fistulising Crohn’s disease (CD), as the severe lack of relevant models hinders research progression. To address this, we present in vitro human IBD mucosal models that recapitulate multiple pathological hallmarks of IBD simultaneously in one model system - immune cell infiltration, stromal remodelling and epithelial disruption. Stimulation of models induces epithelial aberrations common in IBD tissue including altered morphology, microvilli abnormalities, claudin gene expression changes and increased permeability. Inflammatory biomarkers are also significantly increased including cytokines and chemokines integral to IBD pathogenesis. Evidence of extracellular matrix remodelling, including upregulated matrix-metalloproteinases and altered basement membrane components, suggests the models simulate pathological stromal remodelling events that closely resemble fistulising CD. Importantly, MMP-9 is the most abundant MMP and mimics the unique localisation observed in IBD tissue. The inflamed models were subsequently used to elucidate the involvement of TNF-α and IFN- γ in intestinal stromal remodelling, in which TNF-α but not IFN- γ induced MMP upregulation, specifically of MMP-3 and MMP-9. Collectively, our results demonstrate the potential of the IBD models for use in preclinical research in IBD, particularly for fistulising CD.